Kinetical Study of Adsorption Active and Non Activated Carbon from Chocoa Skin in Methyl Violet Solution - Hartono, Tri; Murdiningsih, Hastami; Amri, Amri; Nurhayati, Nurhayati; F, Ramadhani (Politeknik Negeri Ujung Pandang, 2023)
Methyl violet solution has particular color and mostly used to coloring in textiles industry and traditional cloth making.Â The liquid wastes containing this color can be reduces or removed by several methods, one of which is by adsorption using carbon as an adsorbent. The chocoa plant is abundant in Indonesia while its fruit consists of 60.67% lignin, 36.47% selulosa and 18.90% hemiselulosa [1]. Hartono et al. [2 &3] reported cassavaâ€™s skins contain protein, cellulose and crude fiber can be used as basic material (similarly with chocoa skin) of producing active carbon. This research is to develop more on reducing methyl violet (as particular color) containing in liquid waste by adsorbent from chocoa skin with variation of reaction time between active carbon and non-activated carbon for constant particle sizes of 48 Mesh (-425/+250 mm), and also to study the kinetical reaction of chocoa skin active carbon and non-activated carbon for adsorbing methyl violet in term of Freundlich and Langmuir isotherm equations. The result shows the kinetical adsorption of both active and non-activated carbon from chocoa skin as adsorbent follows Langmuir isotherm equation with adsorption capacity of 579.91 mg/g and 338.94 mg/g respectively.Â